2016
DOI: 10.1172/jci76725
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 drives epithelial-to-mesenchymal transition in lung cancer

Abstract: able slope). Kaplan-Meier survival plots and log-rank tests were used to assess differences in outcome. A P value of less than 0.05 was considered significant.Study approval. All animal studies were approved by the Institutional Animal Care and Use Committee at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
206
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(225 citation statements)
references
References 55 publications
14
206
0
5
Order By: Relevance
“…Thus, they may bind to their target genes and recruit other coactivators that lead to upregulation of their target genes. Since ZNF281 is involved in inducing epithelial–mesenchymal transition (EMT) and promotes metastatis [52], anti-oncogenic effects of JQ1 on H23 cells may partly be due to downregulation of ZNF281, presumably through dissociation of BRD2, which may lead to disrupted EMT in lung cancer. Interestingly, a recent study showed that BRD2 activates expression of genes involved in EMT induction, whereas BRD3 and BRD4 exert opposite functions [53], supporting distinct roles of BRD2 among the somatic BET proteins [34,35,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may bind to their target genes and recruit other coactivators that lead to upregulation of their target genes. Since ZNF281 is involved in inducing epithelial–mesenchymal transition (EMT) and promotes metastatis [52], anti-oncogenic effects of JQ1 on H23 cells may partly be due to downregulation of ZNF281, presumably through dissociation of BRD2, which may lead to disrupted EMT in lung cancer. Interestingly, a recent study showed that BRD2 activates expression of genes involved in EMT induction, whereas BRD3 and BRD4 exert opposite functions [53], supporting distinct roles of BRD2 among the somatic BET proteins [34,35,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the role of Spi-B in EMT program induction. Because Spi-B is not able to induce expression of vimentin or EMT-TFs in HBECs, and it has been documented that transformation of HBECs requires series oncogenic mutations and/or genetic manipulation accompanied with microenvironmental induction (36)(37)(38), it is possible that Spi-B may promote EMT through disruption of intercellular junctions, but this effect requires other oncogenic mutations or specific microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…This allows the cells to be prone to TGF-β-induced EMT. The regulatory process of EMT induced by TGF-β in lung adenocarcinoma cells follows the common mechanisms with other types of cancers, which include the contribution of EMTrelated transcription factors, such as Snail and ZEB1 [116,117]. Likewise, TGF-β-induced EMT in lung adenocarcinoma cells is enhanced by co-stimulation with TNF-α or IL-1β secreted by other cells in the tumor microenvironment [118].…”
Section: Tgf-β-induced Target Gene Expression and Emt In Lung Adenocamentioning
confidence: 96%